CATCH COMPOSITION AND ENVIRONMENTAL FRIENDLINESS LEVEL OF SONDONG FISHING GEAR LANDED AT THE FISHERY HARBOR OF RIAU PROVINCE - Dani, Rahma; Brown, Arthur; Nasution, Polaris (Asian Journal of Aquatic Sciences, 2024)
Sondong fishing gear is one of the dominant fishing gear used by fishermen in the UPT Fisheries port of Riau Province Dumai City, which, when operated, can scrape to the bottom of the waters. The specifications of sondong fishing gear affect the catch. This study aimed to determine the composition of catches based on type, length, and weight and explain the level of environmental friendliness of sondong fishing gear that refers to the FAO 1995 CCRF criteria and Taeran 2014 subcriteria. The method used in this research is a survey method, which is conducted by conducting interviews and collecting data directly in the field, then analyzing it using descriptive statistics. The results showed that the composition of the main catch was white shrimp (Penaeus merguiensis), red prawn (P.monodon), and kelong shrimp (P. indicus). At the same time, the bycatch was white pomfret (Pampus argenteus), gulamah (Pseudocienna amovensis), gangetic anchovy (Thryssa mystax), malung (Muraenesox cinereus), stingray (Dasyatis sp), and crab (Portunus pelagicus). The environmentally friendly level of sondong fishing gear, with a value of 16.43 from the interviews with 23 respondents using 8 criteria, states that sondong fishing gear is a category of fishing gear that is not environmentally friendly.